2010
DOI: 10.1016/j.jpainsymman.2009.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Late-Stage HIV/AIDS Patients' and Their Familial Caregivers' Agreement on the Palliative Care Outcome Scale

Abstract: This study compares the self-assessments of 67 late stage HIV/AIDS patients regarding their symptomatology, sense of self-worth and several other aspects of their health care situation, to assessments of that situation provided by their informal caregivers. As part of a dyadic study of care preferences, patients and caregivers independently completed nearly identical versions of the Palliative Care Outcome Scale (POS), a short ten-item measure of the patient's current health, social, and psychological status. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 37 publications
2
28
0
Order By: Relevance
“…In such cases, informal caregivers may be called on to make decisions as the care recipients’ proxy 7,8,9 . Due to recipients’ closer contact with caregivers than with medical providers, caregivers may be in the best position to make medical decisions for care recipients 7,9 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In such cases, informal caregivers may be called on to make decisions as the care recipients’ proxy 7,8,9 . Due to recipients’ closer contact with caregivers than with medical providers, caregivers may be in the best position to make medical decisions for care recipients 7,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies of concordance in ratings between caregivers and care recipients with regard to recipients’ physical and mental health have been focused on cancer caregiving 8,10 . Studies have demonstrated concordance in caregivers’ and care recipients’ ratings of pain and observable physical symptoms, but indicate less agreement on recipients’ mental health status 8,11,12,13 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This decrease in mortality began in 1996 with the provision of free HAART for HIV-infected individuals in Brazil. However, AIDS remains a serious and incurable disease in spite of the therapy, and, when untreated, can lead to death resulting from opportunistic diseases and comorbidities [4]. …”
Section: Introductionmentioning
confidence: 99%